Collective Guilt and Collective Punishment, Individual Responsibility, and Obedience to The Laws - Rubinstein, Lene (Classica et Mediaevalia, 2026)
In his treatise Political Obligation in Ancient Greece and in the Modern World, Hansen addressed the question how far a citizen in a Greek polis had a non-negotiable dut to obey the laws of his community. He argued that several poleis obliged their citizens actively to break the law if their constitution had been overturned or was at threat. The aim of the present paper is to take this discussion further with particular attention to the moral dilemmas that were sometimes faced by citizens whose communities were dependent on external hegemonic powers. The choices confronting such citizens would be particularly difficult if they were living under an imposed constitution, but a choice between obedience and civic obligation might arise even in poleis that had been pressurised into adapting or repealing only specific laws. The discussion will focus on Mytilene, Thebes and the poleis in Keos, as well as on Athens between 405 and 401/0 and in the years after Chaironeia.